Establishment and proliferation under climate change: temperate tunicates in south-western Iceland - Micael, Joana; Rodrigues, Pedro; Ramos-Esplá, Alfonso A.; Gíslason, Sindri (Marine and Freshwater Research, 2022)
Context: Botryllus schlosseri and Diplosoma listerianum are spreading along the south-western coast of Iceland. Both species are non-indigenous and originated from the temperate zone. In some geographic regions, these species have been associated with negative ecological and economic impacts. The proliferation of these colonial tunicates in newly colonised areas will benefit from the projected warming of sea-surface temperatures. Aims: Owing to the influence of temperature in physiological processes of marine invertebrates, the determination of the temporal dynamic of breeding activity is crucial for operational field control actions aiming to keep population abundances below a density-dependent adverse effect. Methods: Colonies of B. schlosseri and D. listerianum were collected during a 12-month period, in Sandgerði, south-western Iceland. The number of oocytes and larvae were counted. Key results: This study showed that both species are present year-round in south-western Iceland. The release of larvae is more intense during the warmer months. Conclusions: To control their population density levels, field actions should be applied during the winter months before the onset of sexual reproduction and recruitment. Implications: In the light of the findings, it is now possible to suggest the best time for countermeasures for both species and optimise resources for marine management.